2024
DOI: 10.3390/ma17030688
|View full text |Cite
|
Sign up to set email alerts
|

Morphology of Microchips in the Surface Finishing Process Utilizing Abrasive Films

Katarzyna Tandecka,
Wojciech Kacalak,
Maciej Wiliński
et al.

Abstract: In this study, the surface of new lapping films was analyzed, and the lapping finishing process was applied to RG7 tin bronze alloy. The research focused on examining lapping films with electrocorundum grains of nominal sizes 30, 12, and 9 μm, commonly used for achieving smooth surfaces. The manufacturing process involves placing abrasive grains and binder onto a polyester tape, resulting in a heterogeneous distribution of abrasive grains. The study investigates the impact of this random distribution on the pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 43 publications
(55 reference statements)
0
6
0
Order By: Relevance
“…In the depressions of the tool's irregularities, large quantities of loose abrasive grains were observed (Figure 9), indicating that all these abrasive grains were torn from the binder and were completely uncontrolled in the machining zone, which could have a very negative effect on the formation of individual deep scratches on the machined surface. It is worth mentioning that abrasive grains embedded and bound in the binder penetrate into the workpiece material to a maximum of 10% of their nominal size [18]. However, such loose grains can cause the formation of much deeper scratches [40,41].…”
Section: Sem Analysis Of Finished Productsmentioning
confidence: 99%
“…In the depressions of the tool's irregularities, large quantities of loose abrasive grains were observed (Figure 9), indicating that all these abrasive grains were torn from the binder and were completely uncontrolled in the machining zone, which could have a very negative effect on the formation of individual deep scratches on the machined surface. It is worth mentioning that abrasive grains embedded and bound in the binder penetrate into the workpiece material to a maximum of 10% of their nominal size [18]. However, such loose grains can cause the formation of much deeper scratches [40,41].…”
Section: Sem Analysis Of Finished Productsmentioning
confidence: 99%
“…For research purposes, the coefficient k was adopted at levels of 0.05 Sz, 0.15 Sz, 0.25 Sz, and 0.35 Sz, where Sz was determined individually for each abrasive film. The authors indicated in the study [40] that during the machining with abrasive films, the abrasive grain penetrates into the workpiece material by approximately 10% of the nominal size of the abrasive grain from which the tool is constructed. Based on the fact that abrasive grains are randomly distributed on the abrasive film, and at certain points, several grains may form abrasive aggregates, such a research range was chosen for cognitive purposes.…”
Section: Evaluation Of the Surface Topography Of Microfinishing Abras...mentioning
confidence: 99%
“…An additional oscillatory motion of the tool was applied, with a frequency of 80 Hz. These are the standard machining parameters [40] for the microfinishing process, compiled in Table 1.…”
Section: Microfinishing Processmentioning
confidence: 99%
See 1 more Smart Citation
“…The challenge lies in determining the critical degree of wear necessary to maintain defect-free cutting edges on electrical steel, preventing the formation of burrs that could potentially create interlayer short-circuit points in the cores of electric machine motors. Efforts are underway to explore methods of cutting electrical sheets and developing tools that mitigate defects in cut edges and preserve the magnetic properties of the sheets [7]. Studies [8,9] investigated the magnetic properties of electrical sheets following laser cutting, EDM, and blanking processes, considering the material's condition after prior processing.…”
Section: Introductionmentioning
confidence: 99%